A same‐day assay predicts apoptotic response to combined BCL‐2 and MCL‐1 BH3‐mimetic targeting in multiple myeloma cells. Issue 1 (20th November 2020) - Grundy, Martin; Al‐Kaisi, Firas; Cull, Joanna; Williams, Cathy; Smith, Dean; Seedhouse, Claire H.
Abstract: Recent advances in treatment options for multiple myeloma (MM) have positive impact on patient survival. However, there is a short fall of rapid and reliable assays that can predict patient response to novel agents. The anti‐apoptotic proteins B‐cell lymphoma‐2 (BCL‐2) and myeloid cell leukaemia‐1 (MCL‐1), are necessary for MM survival, although most myelomas are more dependent on MCL‐1. BCL‐2 inhibition alone yields significant cytotoxicity in only a minority of cases, therefore targeting both proteins simultaneously, is a therapeutic option. Venetoclax and S63845 are BCL‐2 and MCL‐1 targeting BH3‐mimetics which have demonstrated apoptotic synergy in MM. We investigated whether a novel short‐term flow cytometric cytochrome c release assay could predict response to dual BH3‐mimetic targeting in MM cells. Six human myeloma cell lines (HMCL) and seven primary samples were treated with venetoclax and S63845 alone or in combination. The 4‐hour assay confirmed the drug combination was synergistic in all HMCL tested. Annexin‐V data at 48 hours corresponded with 4‐hour response verifying the assay as a predictor of drug sensitivity. All primary samples responded to the drug combination, including samples with 1q gain and t(4;14) translocation. Normal stem cells were unaffected by the drug combination. We have developed a novel assay with the potential to predict response to therapy in MM cells.